2016
DOI: 10.1016/j.jhazmat.2015.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Complete bromate and nitrate reduction using hydrogen as the sole electron donor in a rotating biofilm-electrode reactor

Abstract: Simultaneous reduction of bromate and nitrate was investigated using a rotating biofilm-electrode reactor (RBER) with graphite carbon (GC) rods as anode and activated carbon fiber (ACF) bonded with steel ring as cathode. In RBER, the community of denitrifying bacteria immobilized on the cathode surface could completely utilize hydrogen (H2) as the electron donor, which was internally produced by the electrolysis of water. The short-term test confirmed that the RBER system could reduce 150-800μg/L bromate to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…NO 3 – could have multiple effects on BrO 3 – reduction. NO 3 – might promote BrO 3 – reduction, since nitrate reductases in bacteria are reported to reduce BrO 3 – . , NO 3 – may act as the primary electron acceptor to support the accumulation of bacteria also able to respire BrO 3 – . , NO 3 – might also slow BrO 3 – reduction due to the competition for a scarce electron donor. , Downing et al showed that NO 3 – was reduced prior to BrO 3 – in a hydrogen (H 2 )-based MBfR when H 2 was limiting…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NO 3 – could have multiple effects on BrO 3 – reduction. NO 3 – might promote BrO 3 – reduction, since nitrate reductases in bacteria are reported to reduce BrO 3 – . , NO 3 – may act as the primary electron acceptor to support the accumulation of bacteria also able to respire BrO 3 – . , NO 3 – might also slow BrO 3 – reduction due to the competition for a scarce electron donor. , Downing et al showed that NO 3 – was reduced prior to BrO 3 – in a hydrogen (H 2 )-based MBfR when H 2 was limiting…”
Section: Introductionmentioning
confidence: 99%
“…− reduction due to the competition for a scarce electron donor. 28,29 − in a hydrogen (H 2 )-based MBfR when H 2 was limiting. 30 The first objective of this study was to document BrO 3 − reduction using CH 4 as the sole electron donor and carbon source.…”
mentioning
confidence: 99%
“…The results of the two samples were summed up for the analysis of microbial diversity. The total DNA was extracted using the E.Z.N.A.® Soil DNA Kit (Omega Bio-tek, Norcross, USA) [19]. 16S rRNA genes were amplified using the universal bacteria forward primer 338F (5'-ACTCCTACGGGAGGCAGCAG-3') and reverse primer 806R (5'-GGACTACHVGGGTWTCTAAT-3'), which were targeting the V3-V6 hypervariable regions.…”
Section: Biofilm Sample Collection and Analysismentioning
confidence: 99%
“…Biofilm electrode reactors (BERs) have been studied by various researchers as an effective means of removing pollutants in wastewater treatment processes [1][2][3][4]. In such applications, water electrolysis produces hydrogen gas (H 2 ), which can be utilized by microorganisms on the surface of the cathode as an electron donor [5].…”
Section: Introductionmentioning
confidence: 99%